Proses Hidrolisis Biji Cempedak dengan HCL untuk Bahan Baku Pembuatan Bioethanol - Yuliani, Aliyah; Fadia, Dinda; Amin, Jaksen M.; Dewi, Erwana (Penerbit Goodwood, 2024)
Purpose: This study aims to determine what variables affect during hydrolysis, and the results of this hydrolysis process will be tested for raw materials in making Bioethanol Research methodology: The research was carried out for 3 months, namely April – June 2023, which was carried out at the Laboratory of the Chemical Engineering Department of the Sriwijaya State Polytechnic, Palembang. Results: The ethanol content obtained from the hydrolysis of cempedak seeds is 28.37%.. Conclusion: The highest brix value of 8.7% was obtained at 100 minutes of hydrolysis with 3% HCl concentration. GC-MS results showed an ethanol content of 28.37% with a refractive index of 1.335. Limitations: One of the main limitations of this study might be related to the laboratory-scale nature of the research. Many studies are conducted on a small scale and have not been applied to industrial-scale production. This can be a constraint because a hydrolysis process that works at a small scale may not be easily translatable to mass production. Contribution: This article contributes to the utilization of agricultural waste, specifically cempedak seeds, which are often discarded or underutilized. This has the potential to reduce waste and add value to a product previously considered useless.